Culinary Center in Dalegan Gresik, East Java with a Wave Metaphor Architecture Approach - Scholicha, Ni’matus; Widjajanti, Wiwik Widyo; Poedjioetami, Esty (ADBE, 2021)
Tourism sector has potential of development as it belongs to one of regional revenue sources for Gresik Regency. One of tourism sectors that has great potential is culinary tourism. To Gresik Regency, improving tourism is possible to do because total visits of culinary tourism get increasing from year to year. Unfortunately, a specific culinary site which can accommodate typical food of Gresik has not been available yet. Therefore, the researcher planned and designed Culinary Centre in Dalegan Gresik, East Java under the theme of metaphoric architecture. To collect the research data, several methods were employed such as field study, literature study, and descriptive analysis. The macro concept of recreational is implemented by adjusting the title in the tourism site through the micro concept of dynamic land order having relaxed elements. The micro concept of shape accommodates wavy metaphor of sea water. Thus, this design is expected to be used as the basis for Gresik development so that it becomes a tourism object which can provide food-based recreational service and entertainment to all tourists